Pediatric Advanced Life Support Case 10-A Fussy Baby - Kathleen Ventre (Association of American Medical Colleges, 2012)
Abstract A healthy 1-month-old term infant presents to the emergency department with intermittent fussiness and poor feeding. She is somewhat dusky at the time of her initial assessment. She is afebrile, breathing well, and has a HR of 228, with normal blood pressure. You must recognize supraventricular tachycardia and treat by offering supplemental oxygen and adenosine. Our institution has a full-scale mannequin simulator laboratory with a curricular focus on interdisciplinary, team-based management of pediatric medical emergencies. The majority of providers in our hospital who regularly train in the mannequin laboratory use these computer scenarios to prepare for their team training, and the vast majority of these individuals feel it prepares them to do better during their team training exercises. During the usability testing conducted at our institution, 95% of individuals who completed the pediatric advanced life support cases on a computer simulator felt that it was an effective training experience.